Neural crest cells pattern the surface cephalic ectoderm during FEZ formation - Hu, Diane (2012)
Multiple Fibroblast growth factor (Fgf) ligands are expressed in the forebrain and facial ectoderm, and Vascular Endothelial Growth Factor (VEGF) is expressed in the facial ectoderm. Both pathways activate the MAP kinase cascade and can be suppressed by SU5402. We placed a bead soaked in SU5402 into the brain after emigration of neural crest cells was complete. Within 24 hours we observed reduced pMEK and pERK staining that persisted for at least 48 hours. This was accompanied by significant apoptosis in the face. By day 15 the upper beaks were truncated. Molecular changes in the FNP were also apparent. Normally, Shh is expressed in the Frontonasal Ectodermal Zone and controls patterned growth of the upper jaw. In treated embryos Shh expression was reduced. Both the structural and molecular deficits were mitigated after transplantation of FNP-derived mesenchymal cells. Thus, mesenchymal cells actively participate in signaling interactions of the face, and the absence of neural crest cells in neurocristopathies may not be merely structural.